Edukasi Tentang Pentingnya Makanan Sehat Untuk Mencegah Penyakit Pada Masyarakat Kelurahan Banjar Mlati Kota Kediri - Abbas, Akhmadi (UPT Penerbitan Universitas Jember, 2023)
Background: The high number of cases of non-communicable diseases in Indonesia is caused by various factors, one of which is the behavior of consuming unhealthy foods such as fast food and a lack of consumption of fruits and vegetables. This is because people's understanding is still lacking related to healthy food. Method: The form of this activity is in the form of direct counselling to the community in the form of lectures about the importance of healthy food. Results: The level of public knowledge before being given education was 43% of people with moderate knowledge levels and 57% in the middle of high knowledge levels. While the level of public knowledge after being given education is 40% of people with moderate levels of knowledge and 60% with high levels of knowledge. Conclusion: Education can increase people's knowledge about the importance of healthy food.Keywords: education, healthy food, prevent disease